Association of age at first sexual intercourse and lifetime number of sexual partners with cardiovascular diseases: a bi-directional Mendelian randomization study - Zhuo, Chengui; Chen, Lei; Wang, Qiqi; Cai, Haipeng; Lin, Zujin; Pan, Huili; Wu, Meicui; Jin, Yuxiang; Jin, Hong; Zheng, Liangrong (Frontiers in Cardiovascular Medicine, 2023)
Background: Limited studies have explored the association between sexual factors (age at first sexual intercourse [AFS] and lifetime number of sexual partners [LNSP]) and cardiovascular diseases (CVDs), leaving the causality inconclusive.We performed a bi-directional Mendelian randomization (MR) study to investigate the causality between sexual factors and CVDs, including coronary artery disease (CAD), myocardial infarction (MI), atrial fibrillation (AF), heart failure (HF), and ischemic stroke (IS). Single-nucleotide polymorphisms for sexual factors were extracted from the UK Biobank. Statistics for each CVD were derived from two different databases. MR estimates were calculated per outcome database and were combined through meta-analysis. Several complementary sensitivity analyses were also performed.The primary analysis suggested that AFS was causally associated with the risk of CVDs; the odds ratios (ORs) ranged from 0.686 (95% CI, 0.611-0.770) for HF to 0.798 (95% CI, 0.719-0.886) for AF. However, the association between AFS and IS (OR, 0.844; 95% CI, 0.632-1.126) was not consistent in the meta-analysis after excluding SNPs related to confounders. Moreover, non-significant associations were found between LNSP and CVDs. Reverse direction MR analysis showed that CVDs were not associated with sexual factors.Conclusions: Genetic evidence suggested that AFS was causally associated with the risk of CVDs except for IS, whereas non-significant association of LNSP with CVDs was detected. Further investigation into AFS could be warranted in preventing the progression of CVDs.